Presentation of the dossier: Social Work in times of global crisis - Racines C., Martha (2025)
The Revista Ciencias Sociales presents articles that critically analyze Social Work in Latin America under modern capitalism, focusing on the need for a transformative practice beyond the market. The experiences of Argentina, Chile and Colombia during import substitution industrialization are examined, and the challenges posed to the profession by neoliberalism and authoritarian regimes are discussed. The authors advocate a critical perspective, based on Marxist thought, which prioritizes collective research and resistance to neoliberal policies, to achieve a critical hegemony in the field of Social Work. The journal seeks to contribute to the formation of professional networks committed to social transformation